Soil loss tolerance assessment under different land uses in submontane Punjab - CHANDEL, SUMITA; HADDA, M. S. (Journal of Soil and Water Conservation, 2018)
The submontane Punjab suffers from water erosion which is affected by runoff pathways, soil erosion and deteriorating soil quality. In the area, assessment of soil loss tolerance assumes significance in designing appropriate hydrological structures, soil management and strategies necessary to maintain soil sustainability. Keeping these points in view the study was conducted for the assessment of soil loss tolerance using five factor score (pH; organic carbon, OC; bulk density, Db; infiltration rate, IR and soil erodibility, K-factor of USLE) under different land uses viz., bare, cultivated, grasses, horticulture and forest. Soil loss tolerance was maximum under land use forest (12.5 Mg ha-1 y-1) followed by horticulture (12.2 Mg ha-1 y-1), grasses (12.0 Mg ha-1 y-1), cultivated (10 Mg ha-1 y-1) and minimum under the land use bare (8.2 Mg ha-1 y-1). The findings revealed that the land use forest is the most effective to combat the problem of soil erosion in the area. In the paper the methodology suggested for assessment of soil loss tolerance under a land use could be applied on a larger scale. This will be helpful in environmental planning and management.